2023
DOI: 10.3389/fspor.2023.948919
|View full text |Cite
|
Sign up to set email alerts
|

Contribution and effectiveness of ski and pole forces in selected roller skiing techniques on treadmill at moderate inclines

Abstract: BackgroundMost of the studies about the effects of incline on cross-country skiing are related to the metabolic efficiency. The effective skiing biomechanics has also been indicated to be among the key factors that may promote good performance. The aims of this study were to provide biomechanical characteristics and investigate the relative contribution and effectiveness of ski and pole forces in overcoming the total external resistance with double poling (DP) and Gear 3 (G3) techniques at varying moderate uph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The uphill slopes for the roller skiing and on-snow skiing tests in the current study were different. Previous studies have shown that the cycle characteristics of the DS technique [ 40 ] and other skiing techniques [ 41 , 42 ] were affected by the increasing incline. The results of this study are different from previous results, which may be due to the fact that the skiing speed was not strictly controlled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The uphill slopes for the roller skiing and on-snow skiing tests in the current study were different. Previous studies have shown that the cycle characteristics of the DS technique [ 40 ] and other skiing techniques [ 41 , 42 ] were affected by the increasing incline. The results of this study are different from previous results, which may be due to the fact that the skiing speed was not strictly controlled in this study.…”
Section: Discussionmentioning
confidence: 99%